Cinema que inventa o território : ocupações urbanas através de auto encenações da juventude - Rafael de Amorim Albuquerque e Mello (2022)
The research is based on audiovisual experiences involving the Coletivo Caranguejo Tabaiares Resiste, from a community with the same name in Recife, and the MLB of Minas Gerais. Through filmmaking workshops, it is evident how the youth appears as a decisive actor in the search for recognition and construction of a collective self-image in the midst of dispute scenarios, in the case of these films, involving the right to housing threatened by the advance of real estate speculation in the respective locations. We make a comparison movement, bringing these films closer to other productions made in different times, places and contexts of modern Brazilian cinema. Precisely, we bring the films Couro de Gato (Joaquim Pedro de Andrade, 1962) and Lacrimosa (Aloysio Raulino and Luna Alkalay, 1969). The link between apparently so distant films reveals itself in youth as a common point of a popular figuration placed in a conflict catalyzed by the wide-ranging social inequality in our country, which emerges to the screens in audiovisual experiences. Faced with the differences between the films, we propose a risky neighborhood that crosses the modulations in which this youth plays himself in front of the camera in scenes of conflict. We will focus on the gestures, movements, looks, postures of these actors/actresses-characters who stage themselves in order to form scenic arrangements that allow the comparison and development of the analysis of the films. Three central scenic arrangements are proposed, namely the Run , Face and Coletive.